Hyperexcitability in Spinal WDR Neurons following Experimental Disc Herniation Is Associated with Upregulation of Fractalkine and Its Receptor in Nucleus Pulposus and the Dorsal Root Ganglion - Daniel Pitz Jacobsen; Aurora Moen; Fred Haugen; Johannes Gjerstad (International Journal of Inflammation)
Introduction. Lumbar radicular pain following intervertebral disc herniation may be associated with a local inflammatory response induced by nucleus pulposus (NP) cells. Methods. In anaesthetized Lewis rats, extracellular single unit recordings of wide dynamic range (WDR) neurons in the dorsal horn and qPCR were used to explore the effect of NP application onto the dorsal nerve roots (L3–L5). Results. A clear increase in C-fiber response was observed following NP conditioning. In the NP tissue, the expression of interleukin-1β (IL-1β), colony stimulating factor 1 (Csf1), fractalkine (CX3CL1), and the fractalkine receptor CX3CR1 was increased. Minocycline, an inhibitor of microglial activation, inhibited the increase in neuronal activity and attenuated the increase in IL-1β, Csf1, CX3L1, and CX3CR1 expression in NP tissue. In addition, the results demonstrated an increase in the expression of TNF, CX3CL1, and CX3CR1 in the dorsal root ganglions (DRGs). Conclusion. Hyperexcitability in the pain pathways and the local inflammation after disc herniation may involve upregulation of CX3CL1 signaling in both the NP and the DRG.